Collaborative Governance dalam Program Kampunge Arek Suroboyo Ramah Perempuan dan Peduli Anak di Rw 01, Kelurahan Kandangan, Kota Surabaya - Harsen, Rebecca Lorenzia; Shafiya, Nandina Putri; Arofah, Yayuk Nur; Myvara, Veren; Nafi'ah, Binti Azizatun (IAI Nasional Laa Roiba Bogor, 2025)
Violence against children in Indonesia is still a serious issue that requires deep attention. In addition to violence, the low welfare of adolescents is a serious challenge in Indonesia. Seeing the various problems experienced by children, especially at the local level, the Surabaya City Government, through the Women's Empowerment, Child Protection, Population Control and Family Planning Service (DP3AP2KB), launched the KAS-RPA (Kampung Arek Suroboyo Friendly to Women and Children) program. To optimize the implementation of the Kasrpa Program, active collaboration is needed between implementers, including the implementation of the Kasrpa Program implemented in the Kandangan RW 01 sub-district which won the General Champion